63. THE ROLE OF NATIONAL VALUES IN THE DEVELOPMENT OF SPIRITUALITY OF YOUTH - Mazamkulov Eldor is the son of Makhammadkul (Innovative technologies in construction Scientific Journal, 2023)
This article reveals the importance of national values in the spirituality of young people and the extent to which spirituality is strengthened due to values. It is explained that national values are the basis of nation and society.